Self centering structural systems with combination of hysteretic and viscous energy dissipations. - Kam, Weng Yuen (Earthquake engineering & structural dynamics.)
This paper presents an innovative set of high seismic resistant structural systems termed Advanced Flag Shaped (AFS) systems, where self centering elements are used with combinations of various alternative energy dissipation elements (hysteretic, viscous or visco-elastic plastic) in series and/or in parallel. AFS systems is developed using the rationale of combining velocity dependent with displacement dependent energy dissipation of self centering systems, particularly to counteract near fault earthquakes. Non-linear time history analyses (NLTHA) on a set of four single degree of freedom (SDOF) systems under a suite of 20 far field and 20 near fault ground motions are used to compare the seismic performance of AFS systems with the conventional systems. It is shown that AFS systems with a combination in parallel of hysteretic and viscous energy dissipations achieved greater performance in terms of the three performance indices. Furthermore, the use of friction slip in series of viscous energy dissipation is shown to limit the peak response acceleration and induced base shear. An extensive parametric analysis is carried out to investigate the influence of two design parameters, 1 and 2 on the response of SDOF AFS systems with initial periods ranging from 0.2 to 3.0 s and with various strength levels when subjected to far field and near fault earthquakes. For the design of self centering systems with combined hysteretic and viscous energy dissipation (AFS) systems, 1 is recommended to be in the range of 0.8-1.6 while 2 to be between 0.25 and 0.75 to ensure sufficient self centering and energy dissipation capacities, respectively.